International Scientific Conference Energy Management of Municipal Facilities and Sustainable Energy Technologies EMMFT 2018 Volume 2 - Murgul, Vera.; Pasetti, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a collection of the latest studies on and applications for the sustainable development of urban energy systems. Based on the 20th International Scientific Conference on Energy Management of Municipal Facilities and Sustainable Energy Technologies, held in Voronezh and Samara, Russia from 10 to 13 December 2018, it addresses a range of aspects including energy modelling, materials and applications in buildings; heating, ventilation and air conditioning systems; renewable energy technologies (photovoltaic, biomass, and wind energy); electrical energy storage; energy management; and life cycle assessment in urban systems and transportation. The book is intended for a broad readership: from policymakers tasked with evaluating and promoting key enabling technologies, efficiency policies and sustainable energy practices, to researchers and engineers involved in the design and analysis of complex systems. .
Keywords: Computational intelligence; Electric power production; Computational Intelligence; Electrical Power Engineering; Mechanical Power Engineering